2018
DOI: 10.2151/sola.2018-002
|View full text |Cite
|
Sign up to set email alerts
|

JRA-55CHS: An Atmospheric Reanalysis Produced with High-Resolution SST

Abstract: As an additional product of the Japanese 55-year Reanalysis (JRA-55) project, a new global atmospheric reanalysis product, named JRA-55CHS, is under construction. It utilizes quarterdegree sea-surface temperature (SST) as lower-boundary condition with the same data assimilation system as the JRA-55 Conventional (JRA-55C), into which no satellite data is assimilated. The SST data can resolve steep SST gradients along the western boundary currents (WBCs), which are not necessarily well represented in many of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
(31 reference statements)
4
15
0
Order By: Relevance
“…Satellite-derived estimates of convective precipitation are largely accurate in the low latitudes (Ebert et al, 2007;Chen et al, 2013), but the TMPA product is less accurate over the ocean due to the absence of local observations used for gauge adjustments (Sapiano and Arkin, 2009) and south of 40 • S due to limited local crosssensor calibration (Huffman et al, 2006). TRMM often underestimates precipitation in high-latitude regions with significant topography due to difficulties of satellite retrievals over snow-covered surfaces and/or due to the high elevations (Barros et al, 2006;Matthews et al, 2013). TRMM is also known to underestimate light rainfall and drizzle over subtropical and high-latitude oceans (Berg et al, 2010).…”
Section: Precipitationmentioning
confidence: 99%
“…Satellite-derived estimates of convective precipitation are largely accurate in the low latitudes (Ebert et al, 2007;Chen et al, 2013), but the TMPA product is less accurate over the ocean due to the absence of local observations used for gauge adjustments (Sapiano and Arkin, 2009) and south of 40 • S due to limited local crosssensor calibration (Huffman et al, 2006). TRMM often underestimates precipitation in high-latitude regions with significant topography due to difficulties of satellite retrievals over snow-covered surfaces and/or due to the high elevations (Barros et al, 2006;Matthews et al, 2013). TRMM is also known to underestimate light rainfall and drizzle over subtropical and high-latitude oceans (Berg et al, 2010).…”
Section: Precipitationmentioning
confidence: 99%
“…J-OFURO3 is the latest version of this project and contains significant improvements over J-OFURO [6] and J-OFURO2 [7], including accuracy improvements and a new validation scheme [5]. Various parameters in J-OFURO3 have been validated with satisfactory results, such as the sea-surface LHF and SHF [5]; hence, J-OFURO3 is popular and is widely used in various applications [8,9]. J-OFURO3 provides daily net shortwave radiation (R ns ) and net longwave radiation (R nl ) data, and these values can be directly combined to obtain daily sea-surface R n values.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the re-processed and NRT data do not constitute a homogeneous timeseries, OSTIA is favoured over other SST reanalyses owing to its higher spatial resolution. 25 Masunaga et al (2015Masunaga et al ( , 2018 have shown steep SST gradients, unresolved by coarse SST reanalyses, can influence the organization of long-lived rain bands and enhancement or reduction of surface convergence, and this is particularly problematic for atmosphere-only reanalyses as thermal structure and motions in the marine atmospheric boundary later are not well constrained by data assimilation.…”
Section: Boundary Conditions 15mentioning
confidence: 99%